Systematic literature review: a typology of Sustainability Literacy and Environmental Literacy - Sanchez, Sandra-Jennina; Piedrahita Guzman, Yuly; Sosa-Molano, Julian; Robertson, Douglas; Ahern, Sherri; Garza, Tiberio (Frontiers in Education, 2025)
Creating awareness about Sustainability Literacy (SL) and Environmental Literacy (EL) across educational institutions has increasingly captured the attention of researchers. Given the growing yet fragmented literature about SL and EL across academic disciplines, there is a need to expand and connect this knowledge. This research aims to examine the definitions of SL and EL, their association with Education for Sustainable Development (ESD) and Environmental Education (EE) as well as to present a coherent typology of definitions of SL and EL. The study employs a qualitative thematic analysis approach and the PRISMA guidelines for Systematic Literature Reviews (SLRs) using a sample set of 38 articles from the Scopus and Web of Science databases. The results provide a significant understanding of the notions, typology, and learning outcomes of SL and EL in the context of Education for Sustainable Development (ESD), as well as the most cited SL and EL definitions, the most associated concepts to SL and EL, and the most representative collaboration networks by countries. The findings reveal the interconnection of EL, Environmental Education (EE), ESD, and curriculum design, underscoring the need to integrate sustainability principles into the educational curriculum, as well as the integration of SL and Sustainable Development Goals (SDGs) in Higher Education. Finally, this study uncovers an urgent call to enlarge global and local collaboration networks to expand sustainability knowledge worldwide.